Characterization of care for patients with wounds in Primary Care - Isabel Cristina Ramos Vieira Santos; Marcos Antonio de Oliveira Souza; Luciana Naiara Vieira de Andrade; Mariana Pereira Lopes; Mônica Fidelis Ataide de Barros e Silva; Rosimery Tavares Santiago (Universidade Federal do Ceará, 2014)
This study aimed to describe the treatment of patients with wounds in the Primary Health Care. A descriptive research with quantitative approach. Ninety-three Family Health Units of the city of Recife-PE, Brazil, were selected, and 112 nurses were interviewed from July to December 2011. The record book of bandages and procedures and the dressing form were used as an additional source of data. Frequencies, measures of central tendency and dispersion, prevalence and, for continuous variables, the analysis of variance were estimated. The prevalence of patients with wounds was 1.9% of the estimated covered population. Vascular ulcers accounted for 74.1% of the treated wounds. The dressing was predominantly performed by Nursing technicians, and the products available for this procedure did not match the current technological development.